Intracranial Atherosclerosis Coexisting With White Matter Hyperintensities May Predict Unfavorable Functional Outcome in Patients With Acute Cerebral Ischemia - Liu, Haiyan; Pu, Yuehua; Wang, Yilong; Zou, Xinying; Pan, Yuesong; Zhang, Changqing; Soo, Yannie O. Y.; Leung, Thomas W. H.; Zhao, Xingquan; Wong, Ka Sing Lawrence; Wang, Yongjun; Liu, Liping (Frontiers in Neurology, 2020)
Background and Purpose: We aimed to assess the effect of baseline white matter hyperintensities (WMH) on one-year stroke recurrence and functional outcome for patients with intracranial atherosclerosis (ICAS). Methods: We analyzed 2076 patients who were enrolled in the Chinese IntraCranial AtheroSclerosis (CICAS) study. ICAS and WMH was diagnosed by baseline magnetic resonance angiography. The primary outcomes were stroke recurrence and unfavorable functional outcome (modified Rankin Scale score 3–6) at one year. Results: Among 2076 patients included in this study, 1370(65.99%) were men and mean age was 61.70 years. 224(10.79%) patients had no WMH and no ICAS, 922(44.41%) patients had WMH and no ICAS, 157(7.56%) patients had ICAS and no WMH, 773(37.24%) had both WMH and ICAS. During the follow-up period, 87 patients had recurrent stroke and 333 had unfavorable outcome at one year. Compared to WMH (-) ICAS (-) group, the adjusted odd ratios and 95% confidence interval of unfavorable functional outcome were 0.791 (0.470-1.332; p=0.3779) in WMH (+) ICAS (-) group, 1.920 (1.024-3.600; p=0.0421) in WMH (-) ICAS (+) group, and 2.046 (1.230-3.403; p=0.0058) in WMH (+) ICAS (+) group. There was no significant difference for stroke recurrence risk among the four groups. Conclusion: ICAS coexisting with WMH may predict unfavorable functional outcome at one year, but not stroke recurrence.